2019 IEEE International Conference on Software Maintenance and Evolution (ICSME) 2019
DOI: 10.1109/icsme.2019.00024
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Identify Security-Related Issues Using Convolutional Neural Networks

Abstract: Software security is becoming a high priority for both large companies and start-ups alike due to the increasing potential for harm that vulnerabilities and breaches carry with them. However, attaining robust security assurance while delivering features requires a precarious balancing act in the context of agile development practices. One path forward to help aid development teams in securing their software products is through the design and development of security-focused automation. Ergo, we present a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Qin and Sun (2018) propose to use word embeddings of the title and description of the issue as features and use these to train a Long Short-Term Memory (LSTM). Palacio et al (2019) propose to use the SecureReqNet (shallow) 2 Kallis et al (2019) created the tool Ticket Tagger that can be directly integrated into GitHub as a recommendation system for issue type classification. The Ticket Tagger uses the fastText Facebook AI Research (2019) algorithm, which uses the text as input and internally calculates a feature representation that is based on n-grams, but not of the words, but of the letters within the words.…”
Section: Supervised Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Qin and Sun (2018) propose to use word embeddings of the title and description of the issue as features and use these to train a Long Short-Term Memory (LSTM). Palacio et al (2019) propose to use the SecureReqNet (shallow) 2 Kallis et al (2019) created the tool Ticket Tagger that can be directly integrated into GitHub as a recommendation system for issue type classification. The Ticket Tagger uses the fastText Facebook AI Research (2019) algorithm, which uses the text as input and internally calculates a feature representation that is based on n-grams, but not of the words, but of the letters within the words.…”
Section: Supervised Approachesmentioning
confidence: 99%
“…The network is still a deep neural network, the (shallow) means that this is the less deep variant that was used in byPalacio et al (2019), because they found that this performs better. neural network based on work byHan et al (2017) for the labeling of issues as vulnerabilities.…”
mentioning
confidence: 99%
“…We also added the "I Don't Know" option to the Likert questions to not force the respondents to answer the statements that they were unsure about or were unclear to them. We leveraged the survey studies [37], [38] used to evaluate the usefulness of (the outputs of) ML/DLbased approaches and tools in the software engineering community to design the following statements.…”
Section: Approachmentioning
confidence: 99%
“…We recognized 21 papers proposing solutions to various requirements classification tasks. Most of them focused on Functional/Non-Functional classification tasks [39,40,41,10,11,42,43,44,45,46,47,48,49], while the remaining focused on other classification tasks: security/Not security [50,51,52], topic-based classification [53], and classification based on requirements importance level [54].…”
Section: Requirements Analysismentioning
confidence: 99%